2021
DOI: 10.3389/fmars.2021.633057
|View full text |Cite
|
Sign up to set email alerts
|

Demo-Genetic Approach for the Conservation and Restoration of a Habitat-Forming Octocoral: The Case of Red Coral, Corallium rubrum, in the Réserve Naturelle de Scandola

Abstract: Marine protected areas (MPAs) are one of the most efficient conservation tools to buffer marine biodiversity loss induced by human activities. Beside effective enforcement, an accurate understanding of the eco-evolutionary processes underlying the patterns of biodiversity is needed to reap the benefits of management policies. In this context, integrating population genetics with demographic data, the demo-genetic approach, is particularly relevant to shift from a “species-based pattern” toward an “eco-evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 105 publications
2
7
0
Order By: Relevance
“…grayi . For instance, strong genetic differentiation at small spatial scales and a pattern of isolation by distance are common in many brooding corals in which dispersal potential is generally low given the short duration of the pelagic larval stage and predominantly philopatric recruitment (e.g., Ayre & Hughes, 2000 ; Gazulla et al, 2021 ; Ledoux, Garrabou, et al, 2010 ; Mokhtar‐Jamaï et al, 2011 ; Smilansky & Lasker, 2014 ; Underwood et al, 2007 ; but see discussions in Coelho & Lasker, 2016b ; Jones et al, 2009 ). Interestingly, the spatial genetic patterns described for P. clavata in the Mediterranean (Arizmendi‐Mejía et al, 2015 ; Ledoux et al, 2018 ; Mokhtar‐Jamaï et al, 2011 , 2013 ) coincide with the low effective dispersal inherent to surface brooding inferred from field observations and parental genetic analysis (Coma et al, 1995 ; Mokhtar‐Jamaï et al, 2013 ; but see Guizien et al, 2020 ), while future studies could indicate whether P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…grayi . For instance, strong genetic differentiation at small spatial scales and a pattern of isolation by distance are common in many brooding corals in which dispersal potential is generally low given the short duration of the pelagic larval stage and predominantly philopatric recruitment (e.g., Ayre & Hughes, 2000 ; Gazulla et al, 2021 ; Ledoux, Garrabou, et al, 2010 ; Mokhtar‐Jamaï et al, 2011 ; Smilansky & Lasker, 2014 ; Underwood et al, 2007 ; but see discussions in Coelho & Lasker, 2016b ; Jones et al, 2009 ). Interestingly, the spatial genetic patterns described for P. clavata in the Mediterranean (Arizmendi‐Mejía et al, 2015 ; Ledoux et al, 2018 ; Mokhtar‐Jamaï et al, 2011 , 2013 ) coincide with the low effective dispersal inherent to surface brooding inferred from field observations and parental genetic analysis (Coma et al, 1995 ; Mokhtar‐Jamaï et al, 2013 ; but see Guizien et al, 2020 ), while future studies could indicate whether P .…”
Section: Discussionmentioning
confidence: 99%
“…grayi. For instance, strong genetic differentiation at small spatial scales and a pattern of isolation by distance are common in many brooding corals in which dispersal potential is generally low given the short duration of the pelagic larval stage and predominantly philopatric recruitment (e.g., Ayre & Hughes, 2000;Gazulla et al, 2021;Mokhtar-Jamaï et al, 2011;Smilansky & Lasker, 2014;Underwood et al, 2007; but see discussions in Coelho & Lasker, 2016b;Jones et al, 2009).…”
Section: Genetic Segregation Within the Atlantic Lineagesmentioning
confidence: 99%
“…For example, Waples et al (2018) demonstrated that a massive sampling effort yielded robust N and N e estimates in a large population of bluefin tuna. Additionally, much of the marine dispersal literature has focused on fishes, and this method is promising, but underexplored, in marine invertebrates that exhibit IBD patterns (e.g., Gazulla et al, 2021; Griffiths et al, 2021; Polato et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In this area, the populations of the two species are genetically depleted and isolated with the lowest current effective population sizes. Active restoration actions (e.g., Gazulla et al 2021) should be considered to buffer the impact of genetic drift and putative related adverse effects such as inbreeding depression (Garner et al, 2020). Interestingly, these hot-and coldspots of genetic diversity correspond to the area protected since the longest (1983; almost 50 years) and the shortest (2010; 11 years) period.…”
Section: Conservation Implications: Four Management Units With Contra...mentioning
confidence: 99%
“…Different studies addressed the potential bene ts of these MPAs, yet mainly focused on a large geographic scale (i.e., whole Mediterranean basin) and particular taxa, notably commercial shes (e.g., Blowes et al 2019). In contrast, little is known about the functioning of those protected areas at a regional scale and for ecologically important species, such as habitat-forming species (but see Gazulla et al 2021; ). Because they increase habitat complexity with positive effects on the associated community (Gómez-Gras et al 2021), habitat-forming species are highly relevant targets in conservation biology (Palumbi 2009).…”
Section: Introductionmentioning
confidence: 99%